DIPEPTIDYL PEPTIDASE 4 (DPP-4) INHIBITORS FOR THE TREATMENT OF TYPE 2 DIABETES MELLITUS - Erna Kristin (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
ABSTRACT Diabetes mellitus (DM) is a chronic disease which caused around 1.5 million deaths in 2012. Type 2 diabetes mellitus (T2DM) accounts for 90% of DM worldwide. The prevalence of T2DM is increasing due to obesity. Clinical guidelines recommend the use of metformin as the first-line treatment, followed by the addition of 1 or 2 oral antidiabetic drugs (OADs), such as sulphonylurea (SU), an alpha-glucosidase inhibitor, or thiazolidinediones (TZDs). Recently, newer agents such as dipeptidyl peptidase 4 (DPP-4) inhibitors have been added to those treatment algorithms. The DPP-4 inhibitor is a class of OAD that inhibits the DPP-4 enzyme. Sitagliptin, saxagliptin, vildagliptin and linagliptin are DPP-4 inhibitors available for the treatment of T2DM in Indonesia and many other countries. The DPP-4 inhibitors have similar glycemic efficacy. However, they produce a moderate improvement in glycated hemoglobin (A1C). There are limited numbers of head-to-head trials of DPP-4 inhibitors. In addition, there are no data on the long-term DPP-4 inhibitors use safety (more than two years), mortality, diabetic complications, or health-related quality of life. Although DPP-inhibitors are not used as initial treatment for a majority of patients with T2DM, DPP-4 inhibitors can be used as add-on therapy in T2DM patients who are intolerant to, have contraindications for, or uncontrolled with the use of metformin, SU, or TZDs. The exact role of DPP-4 inhibitors among several other agents to manage T2DM is not clear. There are only a small number of long-term studies on DPP-4 inhibitors assessing the glycemic decrease efficacy, important clinical outcomes (cardiovascular events, mortality), or safety. In patients with chronic renal failure considered to use DPP-4 inhibitors, linagliptin can be recommended. There are inadequate data to assess the effect of DPP-4 inhibitors on the occurrence of acute pancreatitis. Overall, DPP-4 inhibitors are well-tolerated.